Foliar application of N, P, K and Zn for yield enhancement in Kharif maize under rainfed conditions - SHARMA, VIVEK; SANDHU, P.S.; SINGH, M.J. (Journal of Soil and Water Conservation, 2025)
Balanced nutrient management is essential for sustainable crop production and enhances nutrient-use efficiency under rainfed conditions. Foliar application of nutrients is a modern agronomic technology which mitigates the stress in plants under rainfed condition without altering crop productivity. The present study was carried out on rainfed maize crop for two successive seasons with eight treatments i.e. control, water spray, urea(1%), urea(2%), muriate of potash (2%), 19:19:19 fertilizers (1.0%), 19:19:19 fertilizers (1.0%)+ ZnSO4 (0.5%) and ZnSO4 (0.5%). Foliar applications of fertilizers were done at 30 and 45 days after sowing (DAS). The foliar application of fertilizers significantly increased maize yield from 7 to 23% over control treatment. The foliar application of 19:19:19 (1%) + ZnSO4 (0.5%) gave highest yield which was at par with all fertilizer treatments except treatments ZnSO4 (0.5%) and control. The growth parameters i.e. (leaf area index, chlorophyll content, relative leaf water content) and yield attributes (1000 grain weight) also improved significantly in treatment having 19:19:19 (1%)+ZnSO4 (0.5%) which was at par with the foliar application of 19:19:19 (1%) and urea (1&2 %), respectively. The foliar application of 19:19:19 (1%) + ZnSO4(0.5%) improved leaf chlorophyll content, proline content, relative leaf water content, and nutrient uptake, which ultimately increased the maize yield and rain water use efficiency. Among different treatments, net return and B:C was highest in treatment having19:19:19 (1%) + ZnSO4 (0.5%) which gave additional income of Rs 10, 990 ha-1 over the control treatment. Hence, foliar application of 19:19:19 (1%) + ZnSO4 (0.5%) was found to be the best treatment for obtaining the higher maize yield, net return and B:C ratio under rainfed conditions.